Health system responses to the health needs of refugees and asylum-seekers in Malaysia: a qualitative study - Chuah, Fiona Leh Hoon; Tan, Sok Teng; Yeo, Jason; Legido-Quigley, Helena (MDPI, 2019)
Background: This study was conducted to examine the responses and challenges in addressing the health needs of refugees and asylum-seekers in Malaysia from a health systems and policy perspective. Methods: Twenty semi-structured in-depth interviews were conducted with key informants comprising experts, healthcare professionals and program personnel with professional experience in refugee health issues. Deductive and inductive analyses were conducted to identify themes. Results: Our study identified a broad range of actors involved in the response to refugee health locally, of which a greater alignment of interests, collaboration and sharing of responsibility is needed. From a health systems and policy perspective, financial constraints are among the key challenges in addressing the health needs of the refugee and asylum-seeker population in Malaysia. While participants reported high quality healthcare being present in Malaysia, this was not affordable to refugees and asylum seekers. Cultural and language discordance are also key challenges faced by healthcare workers in the delivery of services; accentuating the need for greater cultural competence and language support. Improved access to medication is needed for those with chronic illnesses in order to effectively address the comprehensive health needs of the refugee and asylum-seeker population. Conclusions: Suggested ways forward include adopting a comprehensive health advocacy strategy grounded in the right to healthcare for all; adopting a multi-sectoral approach; tackling the social determinants of health; seeking diversified funding at the global and national level; and improving coordination and collaboration between the various actors.